Numerical Study on the Water Entry Impact Forces of an Air-Launched Underwater Glider under Wave Conditions - Xiangcheng Wu; Xin Chang; Shewen Liu; Pengyao Yu; Lilei Zhou; Wei Tian (Shock and Vibration)
In this study, the water entry of an air-launched underwater glider under wave conditions is numerically simulated by the computational fluid dynamics method. The numerical model is validated by the comparison of nondimensional water entry impact force with published experimental and numerical results. And the influence of water entry points, water entry angles, and water entry attack angles on impact force is studied, which provides guidance for the design of air-launched underwater gliders. The results show that the water entry point has a great influence on the peak value of vertical impact force. In the present study, the peak value of the maximum vertical impact force at different water entry points is almost twice the minimum peak value with the same water entry velocity. The water entry angle at the same water entry point has great influence on the peak value of horizontal impact force, which is mainly related to the horizontal component of the impact velocity. The greater the horizontal component of impact velocity, the greater the peak value of impact force. In addition, the attack angle hardly affects the water entry impact force of the glider with hemispherical head.